Évolution de l’urbanisme et exposition au risque cyclonique à Saint-Martin de 1954 à 2017 - Kelly Pasquon; Gwenaël Jouannic; Julien Gargani; Chloé Tran Duc Minh; Denis Crozier (VertigO)
Hurricanes are common in the French West Indies and particularly on the island of Saint Martin. One can question the inability of society to face up to and recover from the consequences of these events. In this study, we show that between 1954 and 2017 (before Hurricane Irma), Saint Martin had to adapt to numerous constraints, some of which were far more important than hurricanes. In almost 70 years, the population density of the French part of Saint Martin increased from 75 inhab/km² to 668 inhab/km². The majority of this increase occurred in a five years period following the Pons law of 1986 which favoured tax breaks for real estate investment. More than 12 000 buildings were constructed in Saint Martin to welcome the new inhabitants of the island as well as tourists. Many neighbourhoods experienced significant growth which started in the late 1980's. However we observe differences in urban planning, a result of social and territorial segregation which exists on the island. On the one hand, there are private residences in affluent neighbourhoods, on the other hand working-class neighbourhoods with vulnerable dwellings. The effect of hurricanes on this society, which has been highly unequal since the 1960's up to the 1980's, is to reinforce inequalities. The fragile habitats of the poorest populations have been more deeply affected than the richest parts of the population which have been financially supported for reconstruction.